2020
DOI: 10.1007/s00404-020-05683-3
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and vomiting of pregnancy: associations with personal history of nausea and affected relatives

Abstract: Purpose To examine whether personal history of nausea or history of nausea and vomiting of pregnancy (NVP) in relatives are risk factors for a woman to suffer from NVP. Further, to evaluate if these factors are associated with the severity of NVP. Methods Cohort study of 2411 pregnant women recruited from maternity health care clinics. The severity of NVP was categorized according to Pregnancy-Unique Quantification of Emesis (PUQE) questionnaire into no/mild/moderate/severe NVP. History of nausea was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
6
10
2
Order By: Relevance
“…Findings of this study is similar to a previous report of 74.5% from a similar study done in Addis Ababa (Ethiopia) in 2013 [11]. It is however lower than an 88% prevalence reported in a recent study done in Finland [14].…”
Section: Discussionsupporting
confidence: 89%
“…Findings of this study is similar to a previous report of 74.5% from a similar study done in Addis Ababa (Ethiopia) in 2013 [11]. It is however lower than an 88% prevalence reported in a recent study done in Finland [14].…”
Section: Discussionsupporting
confidence: 89%
“…We used nation-wide register data of outpatient visits and inpatient episodes of women admitted for HG, permitting admissions in different services to be merged. In Finland, primary health care is publicly funded and organized in health-care centers, including prenatal care units for pregnancy follow-up [ 48 ]. Virtually, all pregnant women attend routine pregnancy care organized by specialized maternity health-care nurses and midwives, with regular check-ups by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Nausea and vomiting of pregnancy affects approximately 75-80% of pregnant women. 10 Agampodi et al reported that 325 (69.7%) out of 466 pregnant women experienced nausea and vomiting of pregnancy. 19 There is a common ground between nausea and vomiting of pregnancy and vertigo that is a vestibular disorder.…”
Section: Originalmentioning
confidence: 99%
“…The prevalence of nausea and vomiting of pregnancy ranges from 50% to 80%. 10,11 Symptoms range from mild nausea to excessive vomiting to a severe form of nauseavomiting called hyperemesis gravidarum (HG) with electrolyte imbalances, dehydration and weight loss. Nausea and vomiting may cause discomfort in pregnant women in the mildest form but may become a serious threat to the lives of fetus and pregnant woman in the most severe form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation